A Historical Study of Religious Tolerance: A Case Study in Perbulan Village, Laubaleng District, Karo Regency - Aldi Barokah; Hotmatua Paralihan; Kasron Muhsin Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the History of Religious Tolerance: A Case Study in Perbulan Village, Laubaleng District, Karo Regency. The purpose of this research is to describe the history and development of religions and to analyze the forms of religious tolerance in Perbulan Village, Laubaleng District, Karo Regency. The method used in this study consists of heuristics (source collection), verification (source criticism), interpretation, and historiography (writing), based on field research and literature review. The results show that the people of Perbulan Village belong to a pluralistic community, both ethnically and religiously. Christianity and Islam have developed in this village since the early 20th century. The emergence of Christianity in Perbulan Village is inseparable from the role of European missionaries, and during the independence era it continued through evangelists from the Karo ethnic group itself, particularly through various church organizations, especially the Batak Karo Protestant Church (GBKP). Meanwhile, the emergence of Islam in Perbulan Village is closely linked to preachers from Aceh, which was later continued by preachers from the Karo ethnic group, especially the figure of Syaikh Sulaiman Tarigan (1887–1961), and later supported by preachers sent by Islamic mass organizations such as Al-Jam’iyatul Washliyah, Muhammadiyah, Ittihadiyah, and other groups up to the present day. In terms of tolerance values, the community is bound by kinship systems such as rakut sitelu, merga silima, and tutur si waluh jabu, which help prevent social obstacles and horizontal conflicts in community life despite their religious differences.